RELIGIOUS MENTAL HEALTH: A SHIFT TO AN ISLAMIC PSYCHOLOGY - Afifah, Tsaqifa Aulya (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
An understanding of mental health cannot be separated from an idea of ​​being healthy and sick both physically and spiritually. Various studies have revealed that there is a relationship between physical and mental health, where individuals who are calm and peaceful inside tend to have a positive effect on mental health. That will be the important point in this paper. By using the type of library research, this study focuses on two forms of data, namely primary data and secondary data. Primary data obtained from psychological and Islamic literature regarding mental health. While secondary data is obtained by looking at the verses of the Qur'an which discuss mental health. The core study in this article discusses two different concepts of mental health; first is the concept of a healthy soul in the psychological aspect called "Mental Health" and the second is the concept of a healthy mind in the religious aspect called "Nafsul Muthmainnah". Both of them show their interrelationships to realize mental health. The concept of Integration-Interconnection initiated by Amin Abdullah is applied in this study to link psychological studies with Islamic studies which focus on the concept of mental health. The results of this study have given birth to a new term called "Religious Mental Health".